Sahotra Sarkar, Doubting Darwin: Creationist Designs on Evolution (Blackwell Public Philosophy Series). - Schoen, Edward L. (International Journal for Philosophy of Religion, 2008)
The article reviews the book "Doubting Darwin: Creationist Designs on Evolution," by Sahotra Sarkar.